Loan Loss Provision, Good Corporate Governance Dan Manajemen Laba Bank di Indonesia dan Malaysia - Nurshadrina Kartika Sari; Nanda Widaninggar (AFRE (Accounting and Financial Review), 2020)
The development of the banking sector in Indonesia and Malaysia is growing rapidly, fierce business competition encourages management's desire to improve performance and comply with banking regulations with earnings management reported by banks. The aimed of this study provides empirical evidence of the influence of Loan Loss Provision (LLP) and Good Corporate Governance (GCG) on Earnings Management in banks in Indonesia and Malaysia. The research method used is multiple linear regression analysis using a sample of six banks with the largest assets in each country during the 2015-2018 periods. The results of this study prove that (1) LLP and GCG affect earnings management at banks in Indonesia (2) LLP has no effect on earnings management at banks in Malaysia, while GCG affects earnings management at banks in Malaysia. The application of financial accounting standards IFRS 7 on financial instruments requires provision for impairment losses early so as to reduce the need for management in managing earnings; this further strengthens the need for PSAK 71 to be implemented in the banking sector in Indonesia effectively from 2020. In addition, the GCG mechanism in both countries also went well so as to be able to influence the practice of earnings management in banks. DOI: http://doi.org/10.26905/afr.v3i1.4555